PROSTITUTION, GENDER JUSTICE, AND LAW ENFORCEMENT - Linda Sudiono (Justitia et Pax, 2018)
AbstractThe purpose of this research is to investigate the implementation of law enforcement against the criminalization of women commercial sex workers in Parangtritis after enactment of Bantul District Regulation Number 5 of 2007 on the Prohibition of Prostitution and the problem of regulation enforcement of Bantul District Regulation Number 5 of 2007 on the Prohibition of Prostitution. This research is an empirical legal research with a descriptive approach. The results were analyzed with qualitative methods which further draw conclusions with inductive thinking method. The results showed that the application of Bantul District Number 5 of 2007 on the Prohibition of Prostitution is not successful in reducing the number of prostitution in Parangkusumo, Bantul. In addition, the negative impacts were appeared such as the impact of economic, the impact of law certainty, and the impact of the Social Politics on gender mainstreaming in form of inferiority inaugural women’s position in society. The Failure of Bantul District Regulation Number 5 of 2007 on the Prohibition of Prostitution to identify the root of prostitution’s problem is another implementation obstacle.Keywords: District Regulation, Law Enforcement, Prostitution.IntisariTujuan dari penelitian ini adalah untuk mengetahui implementasi penegakan hukum terhadap kriminalisasi perempuan pekerja seks komersial di Parangtritis setelah pemberlakuan Peraturan Daerah Kabupaten Bantul Nomor 5 Tahun 2007 tentang Larangan Prostitusi. Penelitian ini adalah jenis penelitian hukum empiris dengan pendekatan deskriptif. Hasil penelitian dianalisis dengan metode kualitatif dan penarikan kesimpulan dengan metode berpikir induktif. Hasil penelitian menunjukkan pelaksanaan Peraturan Daerah Kabupaten Bantul Nomor 5 Tahun 2007 tentang Larangan Prostitusi tidak berhasil menurunkan angka prostitusi di Parangtritis, Kabupaten Bantul. Di samping itu, Pelaksanaan Peraturan Daerah Nomor 5 Tahun 2007 tentang Larangan Prostitusi menimbulkan beberapa dampak negatif yaitu dampak ekonomi, dampak kepastian hukum dan dampak sosial politik pengarusutamaan gender dalam bentuk inferioritas posisi perempuan dalam masyarakat. Kegagalan Peraturan Daerah Kabupaten Bantul Nomor 5 Tahun 2007 tentang Larangan Prostitusi dalam mengidentifikasi akar kemunculan prostitusi menjadi salah satu penghalang pelaksanaan hukum. Kata Kunci : Peraturan Daerah, Penegakan Hukum, Prostitusi.